2004
DOI: 10.1128/aem.70.4.1973-1981.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria in Water and Loose Deposits of Drinking Water Distribution Systems in Finland

Abstract: Drinking water distribution systems were analyzed for viable counts of mycobacteria by sampling water from waterworks and in different parts of the systems. In addition, loose deposits collected during mechanical cleaning of the main pipelines were similarly analyzed. The study covered 16 systems at eight localities in Finland. In an experimental study, mycobacterial colonization of biofilms on polyvinyl chloride tubes in a system was studied. The isolation frequency of mycobacteria increased from 35% at the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 53 publications
5
112
2
1
Order By: Relevance
“…NTM were observed in drinking water by others using cultivation methods, but the numbers of positive samples ranged from 15% to 83% (8,(38)(39)(40)(41)(42)(43), lower than the 100% positive drinking water samples observed with qPCR in our study. A recent study demonstrated that cultivation methods give an underestimation of NTM in drinking water compared to estimation with qPCR (40).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…NTM were observed in drinking water by others using cultivation methods, but the numbers of positive samples ranged from 15% to 83% (8,(38)(39)(40)(41)(42)(43), lower than the 100% positive drinking water samples observed with qPCR in our study. A recent study demonstrated that cultivation methods give an underestimation of NTM in drinking water compared to estimation with qPCR (40).…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, these results demonstrate that species belonging to the genus Mycobacterium can grow in drinking water (biofilms) at different but low levels of (easily biodegradable) organic carbon in the water. In contrast, by using cultivation methods, it was observed in Finland and the United States that mycobacterial numbers are positively correlated with AOC concentrations (39,43). This apparent discrepancy might be explained by differences in AOC levels, which were considerably higher and had larger ranges in the U.S. and Finnish studies (17 to 234 g C liter Ϫ1 and 38 to 350 g C liter Ϫ1 , respectively) than in our study (3.1 to 28.2 g C liter Ϫ1 ).…”
Section: Discussionmentioning
confidence: 96%
“…Our findings are the first evidence of M. lentiflavum infection reported in Kenya. The main reservoir in the environment has not been firmly established, but organisms with M. lentiflavum-like 16S rRNA gene sequences were detected in soil samples from the UK and from France (Mendum et al, 2000) and the species seem to be frequently present in drinking water distribution systems in Finland (Torvinen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobicity varies between MAC species 64 . Both M. avium and M. intracellulare are recovered more frequently from pipe surfaces in biofilms, than in the planktonic phase 65,66 . However, M. intracellulare forms biofilms more readily than the less hydrophobic M. avium, which is more commonly found in the bulk water 65,67 Despite the global distribution and use of 3T HCUs, whole genome analysis has demonstrated a lack of genetic diversity between isolates 2, 4 .…”
Section: Determining the Source Of Infections Related To Hcusmentioning
confidence: 99%